Tafsir Tarbawi of Restorative Justice in Qur’anic Jinayat Verses; Nahdatul Ulama Pesantren Perspective - Junaedi Junaedi; Muhammad Afifudin Dimyathi; Aswadi Aswadi; Imam Syafi'i; Titik Triwulan Tutik (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This study examines the implementation of restorative justice in Qur’anic jinayat verses (QS. Al-Baqarah 178-179; Al-Maidah 45) through a tafsir tarbawi approach and the Aswaja Nahdlatul Ulama (NU) theological framework within pesantren character education. Employing a mixed-methods Design with 71 respondents 45 from the general public and 26 NU pesantren education experts this study reveals three significant findings. First, islah (reconciliation) and diyat (compensation) are reinterpreted as theological foundations of Islamic restorative justice within pesantren contexts. Second, the NU character education model, based on al-muhāfaẓah ’alā al-qadīm al-ṣāliḥ (preserving valuable traditions) and al-akhdh bi al-jadīd al-aṣlaḥ (adopting beneficial innovations), creates a natural ecosystem for restorative practices. Third, the principle of maqāṣid syarī’ah functions as a harmonizing axis between local ’urf values and global restorative justice norms. Theoretically, the study constructs a Restorative Justice Theology integrating Bayani (textual) and Burhani (rational-contextual) epistemologies characteristic of NU pesantren education. Practically, it provides an operational model for transforming qishāṣ from retribution to restoration, institutionalizing ṣulḥ (reconciliation) in conflict resolution, and aligning character education with SDGs Goal 16 on peace and justice.